Hubungan Antara Konsep Diri dan Penerimaan Perubahan Fisik Pada Remaja Wanita Pada Masa Pubertas - Tanjung, Hoirunnisa; Lestari, Siti; Bahri, Serli; Roza, Siska Desta (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Adolescence is a period of transitional development between childhood and adulthood characterized by rapid growth and development or also called puberty. The most striking changes in adolescent girls are physical changes. The purpose of this study was to determine the relationship between self-concept and acceptance of physical changes in adolescent girls during puberty at SMP Negeri 1 Padangsidimpuan. The type of research used was quantitative with a cross-sectional study approach. The population of the study was all female adolescents in grade VII at SMP Negeri 1 Padangsidimpua. as many as 183 people. The sample in the study was 65 people using the nonprobability sampling method. The analysis used was the Chi-Square test with the results showing that (p = 0.008), meaning that there is a relationship between self-concept and acceptance of physical changes in adolescent girls during puberty. Suggestions for adolescent girls to actively seek information about various physical and psychological changes that occur during adolescence so that adolescents can accept these changes so that a positive self-concept can be formed.